PENERAPAN FILSAFAT HUKUM ISLAM DALAM POLIGAMI (Studi Analisis terhadap PP. No. 10 Tahun 1983 Jo. PP. No. 45 Tahun 1990) - Sylviah Sylviah (Institut Agama Islam Negeri Bone, 2020)
Based on the results, it is found that the philosophy of tasyri 'polygamy in Islam requires the dimension of ontology, epistemology, and axiology to synergize between the historical texts and the historical context so that polygamy becomes a Shari'a that brings benefit to mankind either by do it or by leave it behind. The application of Islamic Law Philosophy to polygamy rules according to Government Regulation number 10 Year 1983 jo Government Regulation number 45 Year 1990 Chapter 4 2nd paragraph on the prohibition of Civil Servants of women to become second/third/fourth wives indicates that shows a law enforcement that in the dimensions of ontology, epistemology and axiology of Islamic law supports its enforcement along with the mission of justice and the benefit of mankind brought by the teachings of Islam itself. mplication of this research is the Philosophy of Islamic Law which is a legal philosophy consisting of three frameworks namely ontology, epistemology, and axiology has provided a comprehensive philosophical and juridical picture of tasyri 'polygamy in Islam and the application of Government Regulation number 10 Year 1983 jo Government Regulation number 45 Year 1990 Chapter 4 2nd paragraph on the prohibition of Civil Servant women become second/third/fourth wife.